Genetic improvement in yield of semidwarf rice cultivars in Colombia - Cuevas Pérez, Federico E.; Berrío Orozco, Luis Eduardo; González Tous, Daniel I.; Correa Victoria, Fernando J.; Tulande Valencia, Edgar (Wiley, 1995)
The narrowing gap between commercial and experimental yields in irrigated rice (Oryza sativa L.) has renewed interest in genetic yieldimprovement. Evaluation of past gains is useful for identifying areas with potential for further enhancement. Tall rice cultivar Bluebonnet 50, introduced semidwarfs ‘IR8’ and ‘IR22’, and 13 semidwarfs developed locally from 1971 to 1989 were grown in Colombia under irrigation and rainfed conditions with and without blast (Pyricularia grisea, Sacc.) control during 1992 and 1993. The objective was to estimate progress from introduction and breeding of semidwarfs. Both types of semidwarfs yielded 80 and 122% more than Bluebonnet 50 under irrigation and rainfed conditions with blast control, respectively. Without blast control, the yield advantage (126%) was significant only in 1993. Tillering of semidwarfs was higher in all environments, ranging from 379 to 721 panicles per square meter versus 173 to 392 panicles per square meter for Bluebonnet 50. Panicles were smaller, ranging from 61 to 95 filled grains per panicle versus 118 to 187 filled grains per panicle for Bluebonnet 50. Mean grain yields of introduced and local semidwarfs were similar, but the latter were 10 to 15 cm taller. Linear regressions of means of local cultivars on year of release were nonsignificant (P > 0.05) for the irrigated and rainfed‐with‐blast control environments. For rainfed conditions without blast control, yield increased 0.13 ± 0.041 ba−1 yr−1; panicle size (1.1 ± 0.4 grains yr−1) and plant height (1.1 ± 0.2 cm yr−1) also increased. Breeding in Colombia has improved adaptation of semidwarf rice to rainfed environments.